Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fnmol.2018.00401
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Heat Shock Protein 90 by 17-AAG Reduces Inflammation via P2X7 Receptor/NLRP3 Inflammasome Pathway and Increases Neurogenesis After Subarachnoid Hemorrhage in Mice

Abstract: Subarachnoid hemorrhage (SAH) is a life-threatening cerebrovascular disease that usually has a poor prognosis. Heat shock proteins (HSPs) have been implicated in the mechanisms of SAH-associated damage, including increased inflammation and reduced neurogenesis. The aim of this study was to investigate the effects of HSP90 inhibition on inflammation and neurogenesis in a mouse model of experimental SAH induced by endovascular surgery. Western blotting showed HSP90 levels to be decreased, while neurogenesis, eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…The NLRP3 inflammasome has been proposed as a regulator of neuroplasticity. The declines in protein expression of NLRP3, ASC, Caspase-1, and IL-1βincreased BDNF and doublecortin (DCX) expressions, as well as BrdU+ cells in the hippocampuses of mice ( Zuo et al, 2018 ). Spatial training reduced the production of NLRP3, Caspase-1, and IL-1β in PR5 mice, which upregulated the expression of synaptophysin, PSD-93, and PSD-95, and enhanced dendritic spine number ( Ren et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 inflammasome has been proposed as a regulator of neuroplasticity. The declines in protein expression of NLRP3, ASC, Caspase-1, and IL-1βincreased BDNF and doublecortin (DCX) expressions, as well as BrdU+ cells in the hippocampuses of mice ( Zuo et al, 2018 ). Spatial training reduced the production of NLRP3, Caspase-1, and IL-1β in PR5 mice, which upregulated the expression of synaptophysin, PSD-93, and PSD-95, and enhanced dendritic spine number ( Ren et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our group have shown the significance of proteostasis chaperones, HSP90 and HSP70/HSPA1A, and transcription factor, heat shock factor 1 (HSF1), in alcohol‐mediated effects on immune cells and liver injury (Ambade et al, 2014; Muralidharan et al, 2014). Recent studies have identified a link between HSP90 and NLRP3 in macular degeneration (Piippo et al, 2018), cerebrovascular disease (Zuo et al, 2018), and HSV infection (Li et al, 2019). Previous studies showed that the NLRP3‐SGT1 (suppressor of the G2 allele of skp1) complex interacts with HSP90 and is important for inflammasome activation (Mayor et al, 2007).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that Hsp90 was involved in apoptosis as well as inflammation in cardiac muscle and neuron cells 29,30 . Recent studies demonstrated that inhibition of Hsp90 by the 17-allylamino-17-demethoxygeldanamycin (17-AAG) or 17-DMAG attenuated UUO, indoxyl sulfate (IS), and high salt-diet-induced renal fibrosis 20,24,31 .…”
Section: Discussionmentioning
confidence: 99%